Web-Based Online Queue Design at Puskesmas Siak Hulu I Kabupaten Kampar-Riau - Devega, Mariza; Zamzami, Zamzami; Darmayunata, Yuvi (Politeknik Ganesha Medan, 2021)
Increasing patient satisfaction in this case, especially Puskesmas as the government agency that provides health services for the community, will certainly have an impact on the quality of service from the Puskesmas Itself. One of them with an efficient queuing system. A good queue will support regularity in an agency. Previously, analysis and calculation of queuing time had been carried out using the Kolgomorov-Smirnov compatibility test at the Puskesmas Siak Hulu I Kabupaten Kampar- Riau, and the results obtained an average of six working hours of patient care. This research is a pilot project that was carried out as a form of increasing effectiveness and efficiency in Puskesmas. The research has been completed and the results are the basis for this research and further research. The purpose of the current research is to make an online queuing system design, where later the results of this design are used to create a web-based online queuing system. The design is adapted to the existing queuing model at the Puskesmas, namely the Sigle Channel-Multi Steps queuing model. System development using System Development Life Cycle (SDLC) consisting of, analysis, design, implementation, and maintenance. The design phase is carried out in three stages, namely conceptual modeling, database design, and interface design. The design starts from making the proposed Rich-Picture, then carries out the predetermined design stages. With this design, it is hoped that in the future it will facilitate the process of developing a web-based online queuing system.